Prevalence of and associations with agitation in residents with dementia living in care homes: MARQUE cross-sectional study - Livingston, Gill (BJPsych Open, 2017)
BACKGROUND: Agitation is reportedly the most common neuropsychiatric symptom in care home residents with dementia. AIMS: To report, in a large care home survey, prevalence and determinants of agitation in residents with dementia. METHOD: We interviewed staff from 86 care homes between 13 January 2014 and 12 November 2015 about residents with dementia with respect to agitation (Cohen-Mansfield Agitation Inventory (CMAI)), quality of life (DEMQOL-proxy) and dementia severity (Clinical Dementia Rating). We also interviewed residents and their relatives. We used random effects models adjusted for resident age, gender, dementia severity and care home type with CMAI as a continuous score. RESULTS: Out of 3053 (86.2%) residents who had dementia, 1489 (52.7%) eligible residents participated. Fifteen per cent of residents with very mild dementia had clinically significant agitation compared with 33% with mild (odds ratios (ORs)=4.49 95% confidence interval (CI)=2.30) and 45% with moderate or severe dementia (OR=6.95 95% CI=3.63, 13.31 and OR=6.23 95% CI=3.25, 11.94, respectively). More agitation was associated with lower quality of life (regression coefficient (rc)=−0.53; 95% CI=−0.61, −0.46) but not with staffing or resident ratio (rc=0.03; 95% CI=−0.04, 0.11), level of residents’ engagement in home activities (rc=3.21; 95% CI=−0.82, 7.21) or family visit numbers (rc=−0.03; 95% CI=−0.15, 0.08). It was correlated with antipsychotic use (rc=6.45; 95% CI=3.98, 8.91). CONCLUSIONS: Care home residents with dementia and agitation have lower quality of life. More staffing time and activities as currently provided are not associated with lower agitation levels. New approaches to develop staff skills in understanding and responding to the underlying reasons for individual resident’s agitation require development and testing. DECLARATION OF INTEREST: None. COPYRIGHT AND USAGE: © The Royal College of Psychiatrists 2017. This is an open access article distributed under the terms of the Creative Commons Non-Commercial, No Derivatives (CC BY-NC-ND) license.